The Correlation between Commitment and Performance of School Counselors - Pedhu, Yoseph; Wibowo, Mungin Eddy; Sugiyo,; Sudarnoto, Laura FN (International Journal of Psychosocial Rehabilitation, 2020)
It is generally accepted that there is a positive correlation between school counselors’ commitment and the quality of their performance. The purpose of this article is to determine the relationships between commitment and performance of school counselors. School counselor commitment and performance are widely considered to impact positively on student achievement and the school. Data were collected from 52 school counselors employed in 42 Catholic High Schools in Jakarta, Indonesia. A quantitative questionnaire, which includes measuring commitment and performance created by the authors, was employed. Means, standard deviation, Pearson correlation was used to analyze the data. The findings of this study indicate that commitment was found to have a significant moderate correlation to the performance of school counselors. The commitment total score showed a positive and strong correlation with performance. Implications for school counselors related to commitment and performance are discussed.